2019
DOI: 10.1007/430_2019_35
|View full text |Cite
|
Sign up to set email alerts
|

Chevrel Phases: Genesis and Developments

Abstract: This chapter summarizes the important role played by Marcel Sergent in the discovery in the Rennes Laboratory of the Chevrel-Phases, which stimulated considerable interest in the international solid state chemistry community, because of their remarkable superconducting properties. After a brief general introduction to this topic the seminal discoveries associated with these phases between 1970 and 1990 are described. After their initial synthesis and structural determination was discovered, it was necessary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 154 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…Eventually, the as-obtained product succeeded in detecting two new phases: FeMo( ii ) 3 S 4 and FeMo( iii ) 2 S 4 . 1 Later, CPs were assigned to these ternary molybdenum–sulfur compounds. In the subsequent 50 years, CPs were prepared using this method extensively.…”
Section: Synthesis Of Cpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the as-obtained product succeeded in detecting two new phases: FeMo( ii ) 3 S 4 and FeMo( iii ) 2 S 4 . 1 Later, CPs were assigned to these ternary molybdenum–sulfur compounds. In the subsequent 50 years, CPs were prepared using this method extensively.…”
Section: Synthesis Of Cpsmentioning
confidence: 99%
“…Chevrel phases (CPs) are ternary molybdenum chalcogenides with a chemical formula M x Mo 6 T 8 (x Z 0), of which T is a chalcogen, and M is a transition metal. 1,2 As shown in Fig. 1, Chevrel et al reported the first preparation of CPs in 1971, 3 which caught widespread attention due to their superconductivity, arousing an upsurge of CP superconducting materials in 1970s-1980s.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of cluster compounds are determined by both the composition and geometry of the cluster core; thus, the search for methods of synthesis of new cluster complexes remains an urgent task in this chemistry. A classical method for the synthesis of cluster compounds of molybdenum, tungsten, and rhenium is high-temperature ampule synthesis from simple substances and binary compounds . In these syntheses, as a rule, chalcogenides and halides of the corresponding metals are used, as well as melts of alkali-metal and alkaline-earth-metal halides.…”
Section: Introductionmentioning
confidence: 99%